PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KADER PINTAR DENGAN PEMANFAATAN APLIKASI PERHITUNGAN GIZI SEBAGAI UPAYA PENANGANAN STUNTING DI KABUPATEN ACEH TAMIANG - Amelia, Amelia; Putri Endah Sari , Herlina; Muliani, Fitra; Fitriani; Fairus (Fakultas Teknik, Universitas Samudra, 2024)
Aceh Tamiang, which is one of the districts ranked 13th out of all districts or cities in Aceh province in 2021. Limited knowledge related to nutritional information, as well as how to identify toddlers indicated stunting is still a problem. So far, a small number of posyandu volunteers have understood and can directly check nutritional status using the application. However, most volunteers only record and measure body weight, and provide additional food to immunization participants, either toddlers or pregnant women. Limited knowledge related to nutritional information, as well as how to identify toddlers indicated stunting is still very lacking. The hope is that there needs to be a strategy from related parties so that stunting prevention can be immediately felt and realized to the fullest, especially in identifying stunting, accessing and disseminating nutritional information. The purpose of this activity is to assist and provide guidance to Posyandu cadres in Alue Ie Puteh Village, Manyak Payed Subdistrict in socializing stunting, nutrition-related information by utilizing IT, namely the android-based nutrition calculation application. The method or approach used is lecture, and direct practice. The results of the PkM activities show that there is an increase in the capacity of cadres in terms of knowledge and skills in using nutritional status applications as an effort to deal with stunting by 92%. Furthermore, 88% strongly agreed that the PkM activities were in accordance with the needs of the partners.